Horseman : a tale of Sleepy Hollow - Henry, Christina, 1974- (Berkley, 2021)
"Revisit the village of Sleepy Hollow and discover that the oldest legends can be the hungriest, in this atmospheric, terrifying new novel from the author of Alice and The Girl in Red. Everyone in Sleepy Hollow knows about the Horseman, but no one really believes in him. Not even Ben Van Brunt's grandfather, Brom Bones, who was there when it was said the Horseman chased the upstart Ichabod Crane out of town-or snuffed out Crane's life by throwing his own head from a fell steed. Brom says that's just legend, the village gossips talking. More than thirty years after those storied events, the village is a quiet place. Fourteen-year-old Ben loves to play "Sleepy Hollow Boys," reenacting the events Brom once lived through. But then Ben and a friend stumble across the headless body of a child in the woods near the village, and the sinister discovery makes Ben question everything the adults in Sleepy Hollow have ever said. Could the Horseman be real after all? Or does something even more sinister stalk the woods?"--